The social construction of sanitary oligarchies in a city of the western Mediterranean: the kairos of a ruling class. Elements of Elche changing society, 1884-1903 - Mariano Monge Juárez (Cultura de los Cuidados, 2013)
The purpose of this paper is to study the health oligarchies and their relationship with the change of society, which is the process of contemporaneización in Elche, a city in the southeast of the peninsula, near the border of the former Kingdom of Valencia with that of Murcia, in the western Mediterranean, during the time of transformation of their means of life and mondos having as reference the period from the opening of the railway and the cholera epidemic in 1884, the origins of the footwear industry and the great strike working in 1903.